A genome‐wide investigation of clinicopathologic endophenotypes uncovers a new susceptibility locus for tau pathology at Neurotrimin (NTM). (1st February 2022) - White, Charles C; Yang, Hyun‐Sik; Schneider, Julie A.; Bennett, David A.; De Jager, Philip L; ,
Abstract: Background: Genome‐wide association studies (GWAS) provide a robust approach for discovery of genes involved in the causal chain of events leading to Alzheimer's disease. The use of clinicopathologic endophenotypes in GWAS is powerful to (1) leverage quantitative traits and (2) provide mechanistic insights into the role of the discovered susceptibility variant. Method: We leveraged genome‐wide genotype data available from the deeply characterized participants in two longitudinal cohorts of age‐related cognitive decline with prospective autopsies: Religious Order Study and Memory and Aging Project. We tested five traits, with up to 1, 332 people tested at 7, 696, 881 SNPs. Result: No novel loci associated with the sloper of cognitive decline, a measure of residual cognition after accounting for pathology, and the burden of amyloid pathology were identified.We identified a novel locus associated with the burden of tau pathology: the rs73035809 variant (p=2.4x10 ‐8 ) is found in an intron of the Neurotrimin (NTM) gene. Further, a previously reported cerebral amyloid antipathy (CAA) risk locus ( UNC5C rs28660566) with suggestive evidence of association reached genome‐wide significance with the increased sample size. Conclusion: We have identified two new ADRD susceptibility variants using an endophenotype approach. NTM is highly expressed in all astrocytic subtypes and OPCs based on single nucleus RNA sequencing; it has previously been implicated in neurite outgrowth. The UNC5C variant helps to orient this previously AD‐associated locus (via a rare coding variant) towards CAA as a potential mechanism by which the locus affects syndromic manifestations of AD. It also illustrates the utility of the endophenotype approach to uncover allelic heterogeneity at known loci which extends our understanding of AD susceptibility. The gene is widely expressed but is enhanced in one subtype of glutamatergic and multiple subtypes of GABAergic neurons. These loci identify new targets that expand the range of potential therapeutic targets.